Bulimia nervosa and treatment-related disparities: a review - Wilson, Kim; Kagabo, Robert (Frontiers in Psychology, 2024)
Bulimia nervosa (BN) is a type of eating disorder disease usually manifesting between adolescence and early adulthood with 12 as median age of onset. BN is characterized by individuals' episodes of excessive eating of food followed by engaging in unusual compensatory behaviors to control weight gain in BN. Approximately 94% of those with BN never seek or delay treatment. While there are available treatments, some populations do not have access. Left untreated, BN can become severe and lead to other serious comorbidities. This study is a review of randomized controlled trials to explore available treatments and related treatment disparities. The objective of this review was to identify differences among treatment modalities of BN and aide in the further treatment and research of bulimia nervosa.This study followed narrative overview guidelines to review BN treatment studies published between 2010 and 2021. The authors used PubMed and PsychInfo databases to search for articles meeting the inclusion criteria. Search terms included phrases such as, BN treatment, BN and clinical trials, and BN and randomized clinical trials.